Factor analysis in cardamom (Elettaria cardamomum Maton) - Madhusoodanan, K M Kuruvilla, J Thomas, V V Radhakrishnan, Priya P Menon, K J (Journal of Spices and Aromatic Crops, 2004)
A pooled factor analysis of 17 variables representing morphological, yield contributing and qualitative characters of 90 genotypes of cardamom (Elettaria cardamomum) was carried out at Myladumpara (Kerala), for identifying marker characters which accommodate the inheritance of associated characters. Among the 17 characters subjected to the analysis, 6 factors were identified as having maximum influence on growth, yield and quality of cardamom. Among the six factors identified, three factors controlled yield and yield contributing characters, two factors controlled qualitative characters and one factor controlled growth characters. The characters identified with maximum factor loadings in each group include bearing tillers clump-I, seeds capsule-I, internodal length, racemes panicle-I, leaf breadth and capsules (dry) kg-I. The six principal components or factors accounted for 78.09% of the total variance.